INNOVATIVE THINKING & FORMAL SYNTHESIS IN THE DESIGN OF MODERN WOMEN'S FABRICS (Al-Academy, 2018)
A study worthy of study and objective analysis of the relationship of formal synthesis and innovative effectiveness in the design of modern women's fabrics, which deals with the first chapter the problem of research based on the following questions: (What role of innovative thinking in the formal synthesis of women's clothing designs Modern) The research objectives included the following:1 - defines the concept of innovative thinking and its effectiveness in design2 - Reveal the role of innovative thinking in the formal synthesis of the designs of modern women's fabrics The theoretical framework which included the following parts:.1 - Innovative thinking in design.2 - Formal synthesis in the designs of modern women's fabrics3 -Formal synthesis of the innovative designs of modern women's fabrics . The research procedures within the third chapter determined the descriptive approach for analyzing the sample samples of (4) models and choosing them according to the objectives of the research. The research tool (analysis form) was prepared and presented to a group of experts and specialists in the field of design, The researcher reached the most important conclusions discussed as follows:The effectiveness of the forces of attraction and excitement achieved through the change in the formal characteristics as a result of the synthesis and its potential to add modifications to the form of reduction and delete and add, to achieve coherence and coherence of the overall design.